Analysis Students’ Speaking Skill Based on Local Material at First Semester in English Department of Unswagati - Afiah, Devi Siti Sihatul (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2016)
The  goals  of  this  research  were: (1) To analyze the students’ mistakes  in speaking skill; (2) To find out the difficulties of local topics in speaking. This  research  used  the  descrivtif  qualitative  method.  The  writer  described  and analyzed the students’ errors in speaking skill  and  the  difficulties  used  the  local materials. The research was carried out at the first year students of english department in 2015/2016 academic year. it was strated from Februari to May 2016. The population was  the  first  semester  students  of  english  department  in  academic  year  of  2015/2016. The number of population was 27 students. The results of this research were: (1) lots of students were able to speak well and few of them were still lack (2) Some of students felt difficult to use some words of local tpoics in speaking